PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM PENDIDIKAN OLAHRAGA PERMAINAN SEPAKBOLA DENGAN TEKNIK MENGGIRING BOLA PADA SISWA KELAS X SMK WERDHI SILA KUMARA - I Made Darmada; Pande Agus Adi Sanjaya (Widyadari, 2025)
This study aims to improve learning outcomes of dribbling skills in soccer games through the application of the Student Team Achievement Divisions (STAD) cooperative learning model in class X students of SMK Werdhi Sila Kumara. The problem faced is the low ability of students in dribbling the ball that has not reached the Minimum Completion Criteria (KKM), caused by the use of conventional learning models. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of the study were 32 class X students, consisting of 18 males and 14 females in the odd semester of the 2024/2025 academic year. Data were collected through observation, skills tests, and documentation, then analyzed qualitatively and quantitatively. The results showed that the STAD model was effective in improving students' dribbling skills. In cycle I, 18 students (56.25%) achieved KKM, while in cycle II it increased to 28 students (87.5%). This increase has met the established success indicators, namely a minimum of 80% of students achieving KKM. Thus, it can be concluded that the application of the STAD type cooperative learning model can improve learning outcomes of dribbling skills in soccer games.